Slovak Republic : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper reviews economic developments in the Slovak Republic during 1994-97. In 1996, a large current account deficit emerged as domestic demand surged by more than 20 percent. At the same time, fiscal policy became expansionary, with the fiscal position turning from surplus to deficit. These imbalances persisted into 1997. In an effort to reverse the deterioration in the external accounts, monetary policy was tightened, but its effectiveness in slowing down domestic demand was undermined by a fiscal policy that became even more expansionary.